Controlling open‐shell loading in norbornene‐based radical polymers modulates the solid‐state charge transport exponentially. Issue 20 (1st August 2017) - Hay, Martha E.; Hui Wong, Si; Mukherjee, Sanjoy; Boudouris, Bryan W.
ABSTRACT: Radical polymers are an emerging class of electronically active macromolecules; however, the fundamental mechanism by which charge is transferred in these polymers has yet to be established in full. To address this issue, well‐defined norbornene‐based nitroxide radical polymers were synthesized using the controlled ring‐opening metathesis polymerization technique. These polymers were blended in solution with a quenched, electrically insulating hydroxylamine derivative to dilute the radical content of the system. Electron paramagnetic resonance spectroscopy data were used to characterize the radical content as well as to reveal that hydrogen atom transfer occurred between the open‐shell and closed‐shell polynorbornene derivatives when they were blended in solution. Using these platform macromolecules, we demonstrate that the systematic manipulation of the radical content in open‐shell macromolecules leads to exponential changes in the macroscopic electrical conductivity. When coupled with the fact that these materials show a clear temperature‐independent charge transport behavior, a picture emerges that charge transfer in radical polymers is dictated by a tunneling mechanism between localized donor and acceptor sites within the redox‐active thin films. These results constitute the first experimental insight into the mechanism of solid‐state electrical conduction in radical polymers, and this provides a design paradigm for open‐shell macromolecular charge transport. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 1516–1525 Abstract : The distribution and concentration of radical sites are systematically controlled in a solid‐state radical polymer thin film. These redox‐active sites serve as the medium for charge transfer in radical polymers, and it is found that electrical conductivity depends exponentially on the loading of these sites. The exponential rise in conductivity as a function of the loading of the radicals, coupled with temperature‐independent conductivity, supports a tunneling charge transfer mechanism. These insights emphasize the critical impact of radical proximity as a design handle for next generation electronic materials.